Conventional Radiology Evaluation of Neonatal Intravascular Devices (NIVDs): A Case Series - Anna Russo; Vittorio Patanè; Lorenzo Faggioni; Alessandro Pinto; Luigia Fusco; Fabrizio Urraro; Emanuele Neri; Alfonso Reginelli (Diagnostics, 2024)
Our radiology department conducted an assessment of 300 neonatal radiographs in the neonatal intensive care unit over almost two years. The purpose was to evaluate the correct positioning of intravascular venous catheters. Our case series revealed that out of a total of 95 cases with misplaced devices, 59 were umbilical venous catheters and 36 were peripherally inserted central catheters. However, all of the central venous catheters were found to be properly positioned. Misplacements of neonatal intravascular devices were found to occur more frequently than expected. The scientific literature contains several articles highlighting the potential complications associated with misplaced devices. Our goal is to highlight the potential misplacements and associated complications that radiologists may encounter while reviewing conventional radiology imaging. Based on our experience, which primarily involved placing UVCs and PICCs, we discovered that conventional radiology is the most effective method for assessing proper device placement with the lowest possible radiation exposure. Given the high number of neonatal vascular device placement procedures, it is essential for radiologists to maintain a high level of vigilance and stay updated on the latest developments in this field.